2015
DOI: 10.1002/2015ja021267
|View full text |Cite
|
Sign up to set email alerts
|

Plasma waves around separatrix in collisionless magnetic reconnection with weak guide field

Abstract: Electrostatic and electromagnetic waves excited by electron beam around the separatrix region are analyzed in detail during the collisionless magnetic reconnection with a weak guide field by using 2‐D particle‐in‐cell simulation with the adaptive mesh refinement. Broadband electrostatic waves are excited both in the inflow and outflow regions around the separatrices due to the electron bump‐on‐tail, two‐stream, and Buneman instabilities. In contrast, the quasi‐monochromatic electromagnetic waves are excited on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The E M values measured by MMS1, MMS3, and MMS4 are nearly identical, consistent with the uniform E M over d i scale in PIC simulations [e.g., Hesse et al ., , ]. The only exception is the departure between 011739.4 and 011739.5 UT due to a double‐layer‐like structure (similar to those reported in prior studies [ Fujimoto , ; Chen et al ., ; Ergun et al ., ]) registered by MMS1 (based on the burst data, not shown). To further substantiate the E M measurement accuracy, note that MMS3 is outside of the EDR in the sheath inflow, detecting an average E M ~ −0.84 mV/m (Figure f′) and −( V e × B ) M ~ −0.71 mV/m.…”
Section: Resultsmentioning
confidence: 98%
“…The E M values measured by MMS1, MMS3, and MMS4 are nearly identical, consistent with the uniform E M over d i scale in PIC simulations [e.g., Hesse et al ., , ]. The only exception is the departure between 011739.4 and 011739.5 UT due to a double‐layer‐like structure (similar to those reported in prior studies [ Fujimoto , ; Chen et al ., ; Ergun et al ., ]) registered by MMS1 (based on the burst data, not shown). To further substantiate the E M measurement accuracy, note that MMS3 is outside of the EDR in the sheath inflow, detecting an average E M ~ −0.84 mV/m (Figure f′) and −( V e × B ) M ~ −0.71 mV/m.…”
Section: Resultsmentioning
confidence: 98%
“…For example, the counter-streaming hot and cold electron populations occurring at reconnection separatrices have been studied extensively with numerical simulations. They have been shown to be unstable to the generation of electrostatic waves, leading to the thermalization of the cold electron beam (Chen et al, 2015;Divin et al, 2012;Egedal et al, 2015;Fujimoto, 2014;Huang et al, 2014). Depending on the velocity at which the waves are generated, they can interact with different parts of the electron distributions (Graham et al, 2015;Omura et al, 1996) and transfer energy between them.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature anisotropy due to betatron acceleration in the dipolarization front flux pileup region has also been observed to grow whistler mode waves [e.g., Fujimoto and Sydora, 2008;Khotyaintsev et al, 2011;Viberg et al, 2014]. Numerical simulations of reconnection have shown double layers on the reconnection separatrix, which can produce ESWs in the form of electron phase space holes [Chen et al, 2015]; the Cluster mission observed these double layers on the separatrix during several magnetopause crossings [Wang et al, 2014]. Buneman instabilities can also lead to the generation of ESWs [Che et al, 2010].…”
Section: Introductionmentioning
confidence: 99%